Empowering nurses to achieve excellence: A VA hospital's journey to Pathway to Excellence® designation. Issue 9 (September 2020) - Rodriguez-Yu, Valerie; Cruz, Amy; Ruiz, Judith; Pickering, Carolyn
Abstract : Follow along as a Texas VA hospital initiates a culture shift toward nursing excellence by creating a positive practice environment and establishing a shared governance model in their quest for Pathway to Excellence designation.